Let's solve the equation step by step.
Step 1: Distribute to get \[ 2(x - 3) + 21 = -3 \] Distributing the 2 we get: \[ 2x - 6 + 21 = -3 \]
Step 2: Combine like terms to get \[ 2x - 6 + 21 = -3 \] Combining \(-6 + 21\) gives us: \[ 2x + 15 = -3 \]
Step 3: Use the (choose a property) to get resulting equation (Response area) We will use the Subtraction Property of Equality to isolate the term with \(x\): \[ 2x + 15 - 15 = -3 - 15 \] This simplifies to: \[ 2x = -18 \]
Step 4: Use the (choose a property) to get resulting answer (Response area) Now we will use the Division Property of Equality to solve for \(x\): \[ \frac{2x}{2} = \frac{-18}{2} \] This simplifies to: \[ x = -9 \]
So the solution is: \[ \boxed{-9} \]